Micro Four‐Layer SiC Coating on Matrix Graphite Spheres of HTR Fuel Elements by Two‐Step Pack Cementation. Issue 11 (4th July 2016) - Zhou, Ping; Liu, Xiaoxue; Zhao, Hongsheng; Li, Ziqiang; Zheng, Zujie; Zhang, Kaihong; Liu, Bing
Abstract : A micro four‐layer SiC coating, which includes inner transition layer, fine‐grained layer, dense bulk layer, and outer loose layer, was fabricated on the matrix graphite spheres of high‐temperature gas‐cooled reactor fuel elements to improve the oxidation‐resistant property by a two‐step pack cementation process. According to the experiment results, the micro four‐layer can be differentiated by SiC grain size and microstructure variation. The oxidation tests at 1773 K for 200 h reveal that the coating structure could effectively improve the oxidation resistance of matrix graphite spheres with a weight gain of 0.52 wt%, and the fine‐grained and dense bulk layers are evidenced as two main antioxidation layers. Although the thermal expansion coefficients of SiC and matrix graphite do not match each other so well, no obvious stress cracking was observed after thermal shocking tests from 1773 K to room temperature for 100 times.